Production of Protease from Aspergillus niger Under Solid State Fermentation Using Different Agro Waste as Substrate - Edelisa Jenny, Radius (Universiti Malaysia Sarawak (UNIMAS), 2018)
Proteases are enzymes that catalyse the hydrolysis of protein into polypeptide and oligopeptide to amino acid. These enzymes have various applications in different industries including detergent, leather, and pharmaceutical production. This study focused on the production of protease enzyme from Aspergillus niger under solid state fermentation (SSF) using different agricultural wastes including pineapple peel, banana peel and corncob as substrate. This study also investigated the effect of different parameters of solid state fermentation on protease production. Amongst the three different agro waste used as the SSF substrate, pineapple peel recorded the highest protease activity (0.089 U) while the lowest was recorded for banana peel (0.061 U). Therefore, pineapple peel was selected as the substrate of further study on the effect of different SSF parameters. The maximum protease activity obtained from pineapple peel was at 6 days of incubation period, 70 % of initial moisture content and at temperature of 35 T.